2016
DOI: 10.1136/inp.i1869
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in small animal oncology

Abstract: Cancer is a common diagnosis in companion animals and, increasingly, clients choose to pursue treatment for their pets. Veterinary oncology is a rapidly growing field and diagnostic and treatment options for animals with cancer are constantly improving and becoming more widely available. Treatment outcomes can be good, but in many cases definitive treatment is not an option and palliative treatment is necessary. This article explores the palliative care of dogs and cats that have been diagnosed with cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 112 publications
1
12
0
Order By: Relevance
“…Only two publications expressly related to horses, 14,15 neither of which were original research studies, while none focused specifically on donkeys or donkey–horse hybrids. This is consistent with other areas of companion animal welfare and veterinary practice, where horses have fallen behind dogs and cats in terms of both research and what is offered 19,24,36 . This in turn is likely to affect interactions between veterinarians and clients depending on the species owned, with Arora et al 17 .…”
Section: Discussionsupporting
confidence: 74%
“…Only two publications expressly related to horses, 14,15 neither of which were original research studies, while none focused specifically on donkeys or donkey–horse hybrids. This is consistent with other areas of companion animal welfare and veterinary practice, where horses have fallen behind dogs and cats in terms of both research and what is offered 19,24,36 . This in turn is likely to affect interactions between veterinarians and clients depending on the species owned, with Arora et al 17 .…”
Section: Discussionsupporting
confidence: 74%
“…Veterinary surgical oncology is a specialization that is increasing in veterinary medicine. Because of better and more widespread veterinary care, companion animals are now more likely to live longer, 4,5 leading to an increase in the number of patients developing cancer over their lifetimes. Animals that are not good candidates for definitive cancer treatment can still undergo palliative therapy, including surgery, and enjoy a relatively good quality of life for their remaining time.…”
Section: Discussionmentioning
confidence: 99%
“…To maximize efficacy and minimize treatment-related morbidity and mortality, the patients must be selected carefully, and treatment goals and their implications must be clearly established. 4,5 This process should be clear to both veterinarians and pet owners. With the increased availability of palliative care solutions, both clinicians and owners must address ethical, medical, social, emotional, and even financial issues.…”
mentioning
confidence: 99%
“…On the other hand, cancer diagnosis of a pet also mobilizes the family. Due to the new meaning given to human-animal interaction, the number of owners who seek cancer treatment for their pets is increasingly higher (Mason, 2016). The same study demonstrated that the existing proximity and emotional bond shift focus from end-of-life care, represented by euthanasia, to other options, such as surgery, chemotherapy and palliative care.…”
Section: Introductionmentioning
confidence: 95%
“…The same study demonstrated that the existing proximity and emotional bond shift focus from end-of-life care, represented by euthanasia, to other options, such as surgery, chemotherapy and palliative care. Veterinary patients can be seen enjoying a good quality of life, in spite of their illness (Mason, 2016).…”
Section: Introductionmentioning
confidence: 99%